Lycium europaeum Extract: A New Potential Antioxidant Source against Cisplatin-Induced Liver and Kidney Injuries in Mice. (5th September 2018) - Rjeibi, Ilhem; Feriani, Anouar; Ben Saad, Anouar; Sdayria, Jazia; Saidi, Issam; Ncib, Sana; Souid, Sami; Allagui, Mohamed Salah; Hfaiedh, Najla
Abstract : This study was designed to assess the protective effects of Lycium europaeum methanol extract (LEM) on liver and kidney injuries induced by cisplatin. The phytochemical composition, the antioxidant activity, and hepatorenal injury biomarkers were investigated. Results revealed that LEM exhibited a significant antioxidant activity in vitro on DPPH radical and H2 O2 scavenging assays. In the animal studies, treatment with LEM significantly reduced the effects of cisplatin intoxication on serum liver biomarkers and serum renal biomarkers. Meanwhile, LEM diminishes significantly the effect of cisplatin on the level of lipid peroxidation in liver and kidney tissues. The activities of the antioxidant enzymes (reduced glutathione, glutathione peroxidase, superoxide dismutase, and catalase) were increased in groups pretreated with LEM and quercetin. Additionally, the normal histological structures of the liver and kidney were restored after treatment with LEM. This work clearly demonstrated that L. europaeum may be useful as a drug with hepato-nephroprotective potentials.